Nanoscale amorphization effect on dislocation emission from an elliptical blunt crack tip in deformed nanocrystalline and ultrafine-grained materials. (July 2019) - Feng, Hui; Tang, Jingwen; Peng, Jun; Wu, Hong
Highlights: Effect of nanoscale amorphization on dislocation emission from a blunt crack is studied. Nanoscale amorphization occurs through splitting transformation of GB disclinations. The criterion for the first dislocation emission form the elliptical blunt crack is derived. Nanoscale amorphization can either enhance or weaken the critical applied SIFs. There is a critical crack-junction distance making the dislocation emission most difficult. Abstract: A theoretical model is established to describe the effect of nanoscale amorphization on the lattice dislocation emission from an elliptical blunt crack tip in deformed nanocrystalline and ultrafine-grained materials. Within the description, the nanoscale amorphization occurs through the splitting transformation of grain boundary disclinations which are produced by grain boundary sliding. The criterion for the first dislocation emission form the elliptical blunt crack is derived. The influence of the nanoscale amorphization and the features of the elliptical blunt crack on the critical stress intensity factors for the dislocation emission are discussed in detail. The obtained results show that the nanoscale amorphization can either enhance or weaken the critical applied SIFs for dislocation emission, depending on the emission angle, the radius of curvature of the elliptical blunt crack and the distance between the nanoscale amorphization and the crack tip. There is a critical crack-junction distance making the dislocation emission most difficult and at this critical crack-junction distance, the stress-release effect of the nanoscale amorphization is strongest.